Regulation of interleukin-6 secretion by the two-pore-domain potassium channel Trek-1 in alveolar epithelial cells - Schwingshackl, Andreas (American Physiological Society, 2013)
We recently proposed a role for the two-pore-domain K(+) (K2P) channel Trek-1 in the regulation of cytokine release from mouse alveolar epithelial cells (AECs) by demonstrating decreased interleukin-6 (IL-6) secretion from Trek-1-deficient cells, but the underlying mechanisms remained unknown. This study was designed to investigate the mechanisms by which Trek-1 decreases IL-6 secretion. We hypothesized that Trek-1 regulates tumor necrosis factor-α (TNF-α)-induced IL-6 release via NF-κB-, p38-, and PKC-dependent pathways. We found that Trek-1 deficiency decreased IL-6 secretion from mouse and human AECs at both transcriptional and translational levels. While NF-κB/p65 phosphorylation was unchanged, p38 phosphorylation was decreased in Trek-1-deficient cells, and pharmacological inhibition of p38 decreased IL-6 secretion in control but not Trek-1-deficient cells. Similarly, pharmacological inhibition of PKC also decreased IL-6 release, and we found decreased phosphorylation of the isoforms PKC/PKDμ (Ser(744/748)), PKCθ, PKCδ, PKCα/βII, and PKCζ/λ, but not PKC/PKDμ (Ser(916)) in Trek-1-deficient AECs. Phosphorylation of PKCθ, a Ca(2+)-independent isoform, was intact in control cells but impaired in Trek-1-deficient cells. Furthermore, TNF-α did not elevate the intracellular Ca(2+) concentration in control or Trek-1-deficient cells, and removal of extracellular Ca(2+) did not impair IL-6 release. In summary, we report the expression of Trek-1 in human AECs and propose that Trek-1 deficiency may alter both IL-6 translation and transcription in AECs without affecting Ca(2+) signaling. The results of this study identify Trek-1 as a new potential target for the development of novel treatment strategies against acute lung injury.